The relationship between ego depletion and work alienation in Chinese nurses: A network analysis - Cui, Yi; Yang, Tianqi; Gao, Hui; Ren, Lei; Liu, Na; Liu, Xufeng; Zhang, Yinling (Frontiers in Psychology, 2022)
Objectives: To investigate the network structure of ego depletion and work alienation in Chinese nurses and identify bridge items to provide suggestions to reduce ego depletion and work alienation. Methods: A total of 353 nurses from three hospitals were enrolled in our cross-sectional study by convenience sampling from June to October 2021 in China. They completed an online survey, which included the Sociodemographic Questionnaire, Nurses' Work Alienation Questionnaire, and Self-Regulating Fatigue Scale. The R packages qgraph, networktools, and bootnet were used to estimate the network model and calculate the indices. Results: The correlation between ego depletion and work alienation was mainly positive. The correlation between "Sometimes I do not know what to do with the work instructions from my superiors" and "I have difficulties remembering things" was the strongest among the cross-community correlations (r = 0.14, P0.01). The bridge strength centrality indices of "Sometimes I do not know what to do with the work instructions from my superiors", "I always feel like a loser" and "I have difficulties remembering things" were the highest (z score = 3.15, 2.83, 1.43). The correlation stability coefficients of the centrality indices were larger than 0.25. Conclusion: Nurses' ego depletion and work alienation are correlated. "Sometimes I do not know what to do with the work instructions from my superiors", "I always feel like a loser" and "I have difficulties remembering things" act as bridges between ego depletion and work alienation communities, and should be the focus of nurses’ psychological tests. Our study provides potential targets for interventions to reduce work alienation from the perspective of ego depletion.